2017
DOI: 10.7717/peerj.3592
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the immediate effects of eccentric heel drop exercise on Achilles tendon and gastrocnemius muscle stiffness using shear wave elastography

Abstract: BackgroundMechanical loading is crucial for muscle and tendon tissue remodeling. Eccentric heel drop exercise has been proven to be effective in the management of Achilles tendinopathy, yet its induced change in the mechanical property (i.e., stiffness) of the Achilles tendon (AT), medial and lateral gastrocnemius muscles (MG and LG) was unknown. Given that shear wave elastography has emerged as a powerful tool in assessing soft tissue stiffness with promising intra- and inter-operator reliability, the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 45 publications
(96 reference statements)
3
27
1
Order By: Relevance
“…After long term exercise, Achilles tendon stiffness was higher than that of infrequent exercisers on nondominant leg but not on dominant ankle 22 . Same results were confirmed after eccentric heel drop exercises 23 .…”
Section: Normal Achilles Tendonsupporting
confidence: 71%
“…After long term exercise, Achilles tendon stiffness was higher than that of infrequent exercisers on nondominant leg but not on dominant ankle 22 . Same results were confirmed after eccentric heel drop exercises 23 .…”
Section: Normal Achilles Tendonsupporting
confidence: 71%
“…An increased level of stiffness detected immediately after an acute mechanical load, may allow for less extension of the tendon [50] which potentially may help reduce macro-trauma risk. Previous research demonstrated that in young healthy ATs, an acute bout of eccentric exercise resulted in a significant increase in AT stiffness as measured with SWE [51]. Other studies however show that a single 30-min bout of running did not impact the stiffness of the AT and concluded that the mechanical properties of tendons remain constant throughout locomotion [23].…”
Section: Discussionmentioning
confidence: 98%
“…For nonruptured Achilles tendinopathy, UE has revealed increased tendon stiffness in response to long-term therapy [23] . These changes can be observed immediately after a therapy session [56] . Specifically, eccentric loading of the Achilles tendon has been shown to immediately induce increased tendon stiffness with SWE [56] .…”
Section: Ue Technology and Tendon-specific Basic Knowledgementioning
confidence: 92%
“…These changes can be observed immediately after a therapy session [56] . Specifically, eccentric loading of the Achilles tendon has been shown to immediately induce increased tendon stiffness with SWE [56] .…”
Section: Ue Technology and Tendon-specific Basic Knowledgementioning
confidence: 92%
See 1 more Smart Citation